Tingkat Pengetahuan Anggota UKM Karate Unesa Terhadap Faktor Cedera, Pencegahan Dan Penanganan Cedera - Atmaja, Aditya Nindya; Yuliastrid, Dita; Susanto, Indra Himawan; Bakti, Ananda Perwira (Universitas Hamzanwadi, 2024)
The purpose of this study was to assess the level of knowledge of Karate UKM members on injuries, injury prevention and injury management. This research method is descriptive quantitative with a sample of 30 people consisting of 20 men and 10 women using the whole sample. The data collection technique uses a questionnaire method with a Likert scale consisting of 40 questions. The results showed the level of knowledge of Karate UKM members on sports injury factors, sports prevention showed in the